Eating habits and dietary acculturation effects among international college students in the United States - Amir Alakaam; Amanda Willyard (AIMS Press, 2020)
Although the United States rates as the top host country for international students in the world, the impact of dietary acculturation on their health status is poorly understood. This study used a qualitative approach to gain an in-depth understanding of the factors related to dietary acculturation among international students in U.S. universities. Ten focus groups, of which eight were in two Midwestern U.S. universities and two in a Southern U.S. university (n = 44), were studied. Participants were international, college-aged students enrolled in U.S. universities. Grounded theory method was used for data analysis to develop themes relevant to dietary changes and factors related to dietary acculturation based on the participants' perspectives and experiences. The results showed that most of the participants faced various dietary challenges and health consequences in the United States. Access to food, religious orientation, time constraints, campus environment, and healthcare access were the main factors influencing student diets. A majority of the students reported weight gain due to eating larger portions, unstructured mealtimes, and frequent snacking. Some students reported that they do not eat fruits and vegetables in the United States because they believe that these foods are not fresh, genetically modified, and may contain pesticides. The majority of participants reported taking unprescribed dietary supplements since moving to the United States. Students who transitioned to the typical American diet reported weight gain, increased fatigue, abdominal discomfort, and other health consequences. Universities should seek to develop policies and programs aimed to reduce the impact of acculturation in order to improve the experience of international students in the United States.